Antimicrobial resistance and geographical distribution of Staphylococcus sp. isolated from whiting (Merlangius merlangus) and seawater in the English Channel and the North sea - Brauge, Thomas; Bourdonnais, Erwan; Trigueros, Sylvain; Cresson, Pierre; Debuiche, Sabine; Granier, Sophie A.; Midelet, Graziella (Environmental pollution (1987), 2024)
Staphylococcus is a significant food safety hazard. The marine environment serves as a source of food for humans and is subject to various human-induced discharges, which may contain Staphylococcus strains associated with antimicrobial resistance (AMR). The aim of this study was to assess the occurrence and geographical distribution of AMR Staphylococcus isolates in seawater and whiting (Merlangius merlangus) samples collected from the English Channel and the North Sea. We isolated and identified 238 Staphylococcus strains, including 12 coagulase-positive (CoPs) and 226 coagulase-negative (CoNs) strains. All CoPs isolates exhibited resistance to at least one of the 16 antibiotics tested. Among the CoNs strains, 52% demonstrated resistance to at least one antibiotic, and 7 isolates were classified as multi-drug resistant (MDR). In these MDR strains, we identified AMR genes that confirmed the resistance phenotype, as well as other AMR genes, such as quaternary ammonium resistance. One CoNS strain carried 9 AMR genes, including both antibiotic and biocide resistance genes. By mapping the AMR phenotypes, we demonstrated that rivers had a local influence, particularly near the English coast, on the occurrence of AMR Staphylococcus. The analysis of marine environmental parameters revealed that turbidity and phosphate concentration were implicated in the occurrence of AMR Staphylococcus. Our findings underscore the crucial role of wild whiting and seawater in the dissemination of AMR Staphylococcus within the marine environment, thereby posing a risk to human health. [Display omitted] •238 Staphylococcus strains were isolated from seawater and whiting.•CoPs showed resistance to at least one of the 16 tested antibiotics.•52% of CoNs exhibited antibiotic resistance; 7 strains were multidrug resistance strains.•Geographical distribution revealed local influences, especially near the English coast.•Turbidity and phosphate correlated with AMR of Staphylococcus.